2015
DOI: 10.3892/br.2015.485
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic postconditioning improves the expression of cellular membrane connexin 43 and attenuates the reperfusion injury in rat acute myocardial infarction

Abstract: Abstract.To investigate the effects of cellular membrane connexin 43 (Cx43) and the potential details in ischemic postconditioning (IPOC)-induced cardioprotection, ischemia/reperfusion (IR) models were generated in 8-week-old male Sprague-Dawley rats by ligating the left coronary artery anterior descending branch. The serum levels of myocardial creatases, nitric oxide (NO) and malondialdehyde (MDA) levels, infarct size, arrhythmia events, expression and distribution of Cx43, ultrastructure and apoptosis in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Previous data have indicated that Cx43 does not appear to be important for cardioprotection during ischemic postconditioning [29]. However, recent studies have demonstrated that ischemic postconditioning decreases the rat infarct size by improving the expression of cellular membrane Cx43 [30]. Although increasing evidence suggests that Cx43 is linked to postconditioning [30-33], no studies have addressed the translocation of Cx43 to the mitochondria during postconditioning.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous data have indicated that Cx43 does not appear to be important for cardioprotection during ischemic postconditioning [29]. However, recent studies have demonstrated that ischemic postconditioning decreases the rat infarct size by improving the expression of cellular membrane Cx43 [30]. Although increasing evidence suggests that Cx43 is linked to postconditioning [30-33], no studies have addressed the translocation of Cx43 to the mitochondria during postconditioning.…”
Section: Discussionmentioning
confidence: 98%
“…However, recent studies have demonstrated that ischemic postconditioning decreases the rat infarct size by improving the expression of cellular membrane Cx43 [30]. Although increasing evidence suggests that Cx43 is linked to postconditioning [30-33], no studies have addressed the translocation of Cx43 to the mitochondria during postconditioning. The experiments presented herein were designed to determine whether postconditioning altered Cx43 in sarcolemmal and mitochondrial fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic conditions can trigger Cx43 hemichannel opening, possibly mediated by the generation of ROS and nitrogen species [ 91 ]. The protection of preconditioning has been confirmed to depend on functional Cx43-formed channels [ 2 ]. Moreover, Cx43 deficiency will lead to ventricular arrhythmia which is the major cause of sudden death in heart failure.…”
Section: The Other Functional Proteins In Mitochondrionmentioning
confidence: 99%
“…As the leading cause of fatality worldwide, ischemic heart diseases (IHD) give rise to widespread loss of cardiomyocytes and subsequent adverse cardiac remodeling [ 1 ]. More than 17 million people had succumbed to IHD in 2008, and the number was estimated to be 23.6 million by 2030 [ 2 ]. Ischemia starves cardiomyocytes of vital oxygen, resulting in severe or irreversible injury to heart [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that repeated transitory opening and closing of the coronary artery before continuous reperfusion of the coronary artery (i.e., ischemic postconditioning) offered relief of ischemic-reperfusion damage and delivered notable protection. Some studies [45, 46] have suggested that ischemic postconditioning could affect the expression of substances such as cellular membrane connexin-43 and nitric oxide (NO).…”
Section: Discussionmentioning
confidence: 99%